2013
DOI: 10.1080/10255842.2012.744396
|View full text |Cite
|
Sign up to set email alerts
|

Impedance-based outflow boundary conditions for human carotid haemodynamics

Abstract: In this study, we develop structured tree outflow boundary conditions for modelling the human carotid haemodynamics. The model geometry was reconstructed through computerised tomography scan. Unsteady-state computational fluid dynamic analyses were performed under different conditions using a commercial software package ADINA R&D, Inc., (Watertown, MA, USA) in order to assess the impact of the boundary conditions on the flow variables. In particular, the results showed that the peripheral vessels massively imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 54 publications
1
33
0
3
Order By: Relevance
“…The branching point is the focus of elevated shear-stress. This elevated tension occurs at the junction between the internal carotid artery, supplying the low-pressure cerebral circulation, and the external carotid branch, providing blood to the high resistance facial muscles [ 8 ]. This vulnerable region is well suited for imaging evaluation and provides an ideal surrogate for other vascular beds.…”
Section: Introductionmentioning
confidence: 99%
“…The branching point is the focus of elevated shear-stress. This elevated tension occurs at the junction between the internal carotid artery, supplying the low-pressure cerebral circulation, and the external carotid branch, providing blood to the high resistance facial muscles [ 8 ]. This vulnerable region is well suited for imaging evaluation and provides an ideal surrogate for other vascular beds.…”
Section: Introductionmentioning
confidence: 99%
“…Fluid-structure interaction (FSI) between the blood flow and the arterial-wall deformation in various arteries has been widely investigated. Malvé et al compared the computational results between rigid and compliant arterial walls and showed that WSS distributions are similar for both CFD and FSI simulations, while qualitative discrepancies in the WSS distribution and relevant differences in the WSS temporal profiles are also available, especially in the areas characterized by high displacement [34]. The temporal variation of WSS shows lower WSS values computed with FSI simulation than the CFD analysis.…”
Section: Discussionmentioning
confidence: 84%
“…Para el cálculo del flujo sanguíneo, se han empleado las ecuaciones de continuidad y de Navier-Stokes, además de realizar el cálculo de varios ciclos cardiacos en estado transitorio a partir de condiciones de contorno de arterias carótidas [2], y la aplicación de la Ley de Murray para la distribución de flujo en las bifurcaciones.…”
Section: Modelo Matemáticounclassified
“…Crecimiento de placa de ateroma en arteria carótida de paciente específico según diferentes estímulos mecánicos Patricia Hernández López 1 , Myriam Cilla Hernández 1,2,3 , Miguel Ángel Martínez 1,3 Barca, Estefanía Peña Baquedano 1,3 1 Applied Mechanics and Bioengineering (AMB) Instituto de Investigación en Ingeniería de Aragón (I3A) Universidad de Zaragoza, Mariano Esquillor s/n, 50018, Zaragoza, Spain.…”
unclassified